Cirrhilabrus shutmani, a new species of fairy wrasse from the Babuyan Islands, northern Philippines (Teleostei: Labridae) - Tea, Yi-Kai; Gill, Anthony C. (Zootaxa, 2017)
Cirrhilabrus shutmani, new species, is described on the basis of four specimens from Didicas Volcano, Babuyan Islands, Cagayan province, northern Philippines. The holotype and three paratypes were collected at a depth of 50–70 m, along denuded rubble slopes. The new species belong to a complex consisting of C. blatteus, C. claire, C. earlei, C. jordani, C. lanceolatus, C. roseafascia, C. rubrisquamis and C. sanguineus. Aside from similar nuptial male colouration, the nine species share the following character combination: relatively short pelvic fins (not or barely reaching anal-fin origin, except for C. claire with relatively long pelvic fins); a pair of stripes on head (in both sexes); and, dorsal and anal fins without obvious stripes or spots. It differs from the other members of its group in lacking any stripes on the upper and lower body, and in having the following live colouration details: upper part of nape dusky red; dorsal and anal fin bright red with dusky markings; pelvic fins bright red, dusky anteriorly; caudal fin bright yellow basally with distal half bright red. We also present new distribution records for C. claire, C. earlei and C. lanceolatus, as well as a brief mention of a possibly new, related species from the Ogasawara Islands.